2016
DOI: 10.1590/1678-4324-2016150357
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Lipase-Catalyzed Transesterification of Cotton Seed Oil for Biodiesel Production Using Response Surface Methodology

Abstract: The aim of this work was to study the biodiesel production from cotton seed oil by lipase produced by Pichia guilliermondii lipase, which was immobilized onto hydrophobic magnetic particles (HMPs). The optimum reaction conditions were determined for lipase dosage, methanol-to-oil molar ratio, temperature and water content. Using response surface methodology, a quadratic polynomial equation was obtained for fatty acid methyl esters (FAMEs) content by multiple regression analysis. Verification experiments confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
(7 reference statements)
2
9
0
2
Order By: Relevance
“…GC-FID, having a highly-polar BPX-70 capillary column (30 m × 0.25 mm), was utilized for the analysis of products. The oven temperature was kept at 100 • C for 30 s, then raised to 250 • C at a rate of 10 • C/min, while the temperature of the detector was set at 270 • C. 500 ppm of sample was dissolved in hexane containing methyl heptadecanoate as an internal standard, and 1 µL of this mixture was injected in column [26,27]. The percentage conversion of biodiesel was calculated by given formula [28]…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations
“…GC-FID, having a highly-polar BPX-70 capillary column (30 m × 0.25 mm), was utilized for the analysis of products. The oven temperature was kept at 100 • C for 30 s, then raised to 250 • C at a rate of 10 • C/min, while the temperature of the detector was set at 270 • C. 500 ppm of sample was dissolved in hexane containing methyl heptadecanoate as an internal standard, and 1 µL of this mixture was injected in column [26,27]. The percentage conversion of biodiesel was calculated by given formula [28]…”
Section: Experimental Designmentioning
confidence: 99%
“…Similar conditions have also been investigated by other researchers. Ying and Dong obtained the maximum biodiesel yield using immobilized lipase with 31.3% nano-biocatalyst, 38 • C temperature and 4.7:1 methanol to oil ratio [27]. Thangaraj et al reported the maximum biodiesel yield of 89% at an optimum condition i.e., 1:3 methanol/oil ratio, 12 h of reaction period and 45 • C temp., using the immobilized NS81006 lipase as the catalyst [45].…”
Section: Optimized Reaction Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Among continuous reactors, the packed-bed reactor (PBR) is one of the simplest configurations, where the immobilized biocatalyst is trapped in the reactor, while the substrate solution is pumped through at a specific flow rate that will determine the residence time. [13][14][15][16] This configuration reduces the process cost, besides showing faster and higher catalytic activity compared to bioreactors using free enzymes. 1,17 The use of solvents in lipase-catalyzed transesterifications depends on the necessity of each process.…”
Section: Introductionmentioning
confidence: 99%